Vascular dysfunction in aged mice contributes to persistent lung fibrosis. Issue 8 (21st July 2020) - Caporarello, Nunzia; Meridew, Jeffrey A.; Aravamudhan, Aja; Jones, Dakota L.; Austin, Susan A.; Pham, Tho X.; Haak, Andrew J.; Moo Choi, Kyoung; Tan, Qi; Haresi, Adil; Huang, Steven K.; Katusic, Zvonimir S.; et al.
Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive disease thought to result from impaired lung repair following injury and is strongly associated with aging. While vascular alterations have been associated with IPF previously, the contribution of lung vasculature during injury resolution and fibrosis is not well understood. To compare the role of endothelial cells (ECs) in resolving and non‐resolving models of lung fibrosis, we applied bleomycin intratracheally to young and aged mice. We found that injury in aged mice elicited capillary rarefaction, while injury in young mice resulted in increased capillary density. ECs from the lungs of injured aged mice relative to young mice demonstrated elevated pro‐fibrotic and reduced vascular homeostasis gene expression. Among the latter, Nos3 (encoding the enzyme endothelial nitric oxide synthase, eNOS) was transiently upregulated in lung ECs from young but not aged mice following injury. Young mice deficient in eNOS recapitulated the non‐resolving lung fibrosis observed in aged animals following injury, suggesting that eNOS directly participates in lung fibrosis resolution. Activation of the NO receptor soluble guanylate cyclase in human lung fibroblasts reduced TGFβ‐induced pro‐fibrotic gene and protein expression. Additionally, loss of eNOS in human lung ECs reduced the suppression of TGFβ‐induced lung fibroblast activation in 2D and 3D co‐cultures. Altogether, our results demonstrate that persistent lung fibrosis in aged mice is accompanied by capillary rarefaction, loss of EC identity, and impaired eNOS expression. Targeting vascular function may thus be critical to promote lung repair and fibrosis resolution in aging and IPF. Abstract : Bleomycin‐induced lung injury promotes transient fibrosis accompanied by increased capillary density in young mice. In contrast, persistent fibrosis, capillary rarefaction, loss of endothelial cell identity, and reduction of Nos3 are observed in aged mice. eNOS/NO signal is an important driver of fibroblast quiescence and fibrosis resolution, that is lost with aging. Lung vascular bed plays a critical role during lung repair and fibrosis resolution.